Critiquing a study or a paradigm?: In response to: The Promise of Allostatic Load Rests Upon Strategic Operationalization, Scoring, and Targeted Interventions. - Kenny, Rose; Mc Crory, Cathal (My University, 2021)
We are thankful to Li and Rosemberg for their commentary on our study and for giving us the opportunity to respond. Firstly, it should be acknowledged that we agree with many of the points raised as their commentary reads more like a critique of the general Allostatic Load literature rather than a specific commentary on our paper. To briefly recap, our study was designed to compare the explanatory utility of a variety of different Allostatic Load scoring algorithms for predicting health outcomes using a panel of 12 biomarkers across 4 physiological systems using a large nationally representative sample of community-dwelling older people. Our results suggested that the choice of Allostatic Load scoring algorithm exerts a relatively modest influence in predicting several important age-related health outcomes, including walking speed and self-reported health.
PUBLISHED
Keywords: Ageing